Structure–Effect Relationships of Novel Semi-Synthetic Cannabinoid Derivatives - Götz, Marcus R.; Collado, Juan A.; Fernández-Ruiz, Javier; Fiebich, Bernd L.; García-Toscano, Laura; Gómez-Cañas, María; Koch, Oskar; Leha, Andreas; Muñoz, Eduardo; Navarrete, Carmen; Pazos, Maria R.; Holzgrabe, Ulrike (Frontiers in Pharmacology, 2019)
Background: As a library of cannabinoid derivatives with (-)-trans-cannabidiol (CBD) or (−)-trans-cannabidivarin (CBDV) scaffold, we synthesized nine novel cannabinoids: 2-HEC, 2-HPC, GCBD, CHC, HC, NMSC, 2-HECBDV, CHCBDV, HCBDV. Their binding and intrinsic effects at the cannabinoid (CB)1- and CB2-receptor and the effects on inflammatory signaling cascades were investigated in in vitro and ex vivo cell models. Materials and methods: Binding affinity was studied in membranes isolated from CB-receptor-transfected HEK293EBNA cells, intrinsic functional activity in CHO cells, and activation of nuclear factor κB (NF-κB) and nuclear factor of activated T-cells (NFAT) in phorbol 12-myristate 13-acetate (PMA)/ionomycin (IO)-treated Jurkat T-cells. Inhibition of interleukin (IL)-17 induced pro-inflammatory cytokines and chemokines (IL-6, IL-1β, CC-chemokine ligand 2 (CCL2), tumor necrosis factor (TNF)-α) was studied in RAW264.7 macrophages at the RNA level. Pro-inflammatory cytokines (IL-1β, IL-6, IL-8, TNF-α) and prostaglandin E2 (PGE2) expression was investigated at the protein level in lipopolysaccharide (LPS)-treated primary human monocytes. Results: Derivatives with long aliphatic side chains at the ester position at R1 (HC [5]) as well as the ones with polar side chains (2-HECBDV [7], NMSC [6], 2-HEC [1]) can be selective for CB2-receptors. The CBDV-derivatives HCBDV and CHCBDV demonstrated specific binding at CB1- and CB2-receptors at nanomolar concentrations. 2-HEC, 2-HPC, GCBD, and NMSC were agonists at CB2- and antagonists at CB1-receptors. 2-HECBDV was an agonist at CB2-receptor and an antagonist at the CB1-receptor. NMSC inhibited NF-κB and NFAT activity, and 2-HEC, 2-HPC, and GCBD dose-dependently inhibited PMA/IO-stimulated NFAT activation. CHC and HC dose-dependently reduced IL-1β and CCL2 mRNA expression. NMSC inhibited IL-1β, CCL2, and TNF-α at lower doses. At higher doses, it induced a pronounced increase in IL-6 mRNA. 2-HEC, 2-HPC, and GCBD dose-dependently inhibited LPS-induced IL-1β, TNF-α, and IL-6 synthesis. NMSC further increased LPS-stimulated IL-1β release, but inhibited IL-8, TNF-α, and PGE2. Conclusion: The CBD- and CBDV-derivatives studied are suitable for targeting CB-receptors. Some may be used as selective CB2 agonists. The length of the aliphatic rest at R2 of CBD (pentyl) and CBDV (propyl) did not correlate with the binding affinity. Higher polarity at R1 appeared to favor the agonistic activity at CB2-receptors.